面向印尼学生的“听说+读写”高效教学模式探析 - Ren Deling (Sinolingua: Journal of Chinese Studies, 2024)
In response to the actual needs of Indonesian students in learning Chinese,Sekolah Tinggi Bahasa Harapan Bersama in Pontianak and the College of Chinese Language and Culture of Jinan University have cooperated to open an efficient teaching model of "listening, speaking + reading and writing", in order to quickly improve students' Chinese use ability in a short period of time. This study intends to compare the efficient model with the traditional Indonesian undergraduate teaching model from the aspects of curriculum setting, teaching content, teaching methods and teaching strategies, so as to better meet the needs of different learners. In terms of curriculum setting, the efficient mode adopts the concept of "small steps and fast walking", and the course type is streamlined into two categories: "listening and speaking" and "reading and writing". In terms of teaching content, the study aims to analyze the differences in the content learned by comparing the number of new words taught in one semester and the difficulty level of the two modes. In terms of teaching methods and strategies, the teaching model of "listening, speaking + reading and writing" proposes teaching strategies including "language 'use' for middle school", 'increasing input' and 'running in small steps'". On the basis of teaching practice, this paper evaluates the practical effect of the effective teaching mode of "listening, speaking + reading and writing" for Indonesian students from the aspects of Chinese proficiency test scores, daily homework and activity performance, and then reflects on and improves the teaching practice.